Trees in the city - Nadel, Ira Bruce; Bohm, Lesley R.; Oberlander, Cornelia Hahn. (New York Pergamon Press, 1977)
Discusses the importance of trees in urban environments and provides a guide to planting trees in the city.
Keywords: Trees in cities